Role of 3 Lipoprotein Lipase Variants in Triglycerides in Children Receiving Highly Active Antiretroviral Therapy. Issue 2 (February 2015) - Colombero, Cecilia; Catano, Gabriel; Rocco, Carlos A.; Mecikovsky, Débora; Bologna, Rosa; Aulicino, Paula C.; Sen, Luisa; Mangano, Andrea
<x xml:space="preserve">Abstract</x> Background: Lipoprotein lipase is a key enzyme in lipid metabolism, especially for plasma triglycerides (TGs). Genetic variants have been associated with lipid levels in healthy individuals, cardiovascular disease, obesity and diabetes. Our aim was to evaluate the influence of 3 polymorphisms: Hind III, Pvu II and S447X in plasma TG levels in human immunodeficiency virus-1-infected children under highly active antiretroviral therapy (HAART). Methods: Fifty-two children diagnosed with human immunodeficiency virus-1 between 2005 and 2009 were retrospectively selected with at least 1 plasma TG level assessment. TG levels were examined before and after 1 year of HAART. Hypertriglyceridemia was defined as TG > 150 mg/dL. Hind III (H+/H−), Pvu II (P+/P−) and S447X (S/X) were determined by polymerase chain reaction and restricted fragment length polymorphism. The Wilcoxon sum-rank test was used to compare median plasma TG among groups. Also, allelic frequencies were estimated for these variants in an Argentinean population. Results: Allelic frequencies for human immunodeficiency virus-1-infected children were: H−, 0.21; P−, 0.53; and X, 0.05 with no significant differences to controls. After 1 year of HAART, median TG levels were significantly lower in P−/P− (98.5 mg/dL) when compared with P+/P+ (180 mg/dL) (P = 0.039). The presence of the P− allele was associated with an 11-fold lower risk of hypertriglyceridemia. Hind III and S447X were not associated with TG at the selected time points. Conclusions: Our findings suggest a protective effect of lipoprotein lipase polymorphisms against hypertriglyceridemia in children after 1 year of HAART. These results could endorse a prompt nutritional or pharmacological intervention in patients lacking the P− allele.